Cellular response in Inflammatory Reaction In the Duck - Valsala K V (Department of Pathology, College of Veterinary and Animal Sciences, 1985)
The cellular dynamics in ducks associated with inflammatory response induced by various immunogenic and non-immunogenic agents was studied for the first time. The inflammatory response was induced in the web of ducks using turpentine, dextran sulphate, talc, Staphylococcus aureus, homologus erythrocytes and Freund’s complete adjuvant. The biopsy specimens were collected from half an hour up to 21 days at specific time intervals and examined to assess the cellular response and the chronology of cellular events taking place during the emigration process was depicted. The comparative features of cellular events taking place when different agents were employed were also clarified. The light microscopic studies were supported by electron microscopic studies. Irrespective of the agents employed to elicit the inflammatory reaction it was found that there was emigration of heterophils and monocytoid cells from the arterioles and venules concurrently even though there was quantitative difference in the number of emigrating cells due to different agents. Initially there was high predominance of heterophils in the exudate and later there was predominance of macrophages or lymphocytes. Participation of basophils was also evident at the initial stages. Lymphoid foci formation with germinal centres particularly when antigenic stimulus was used was a characteristic feature. It was demonstrated that monocytoid mononuclear cells transformed into macrophages, epithelioid cells and giant cells. The morphological features of the heterophilic granules were studied by electromicroscopy. Large dense granules with one or two electron dense core and light granules with fibrillary matrix were seen. The process of endocytosis of the foreign body involved fusion of phagosomes. The active heterophil was demonstrated to contain more glycogen. The transformation of monocytoid cells into macrophages was demonstrated to be associated with increase in size and number of endoplasmic reticulum and formation of well developed golgi complex and lysosomes. Epithelioid cells were devoid of phagolysosomes. It was clarified that the lymphocytes underwent transformation into plasma cells under antigenic stimulation. The plasmacytoid transformation was evidenced by formation of rough surfaced endoplasmic reticulum. The systemic response to Ranikhet disease virus and Duck plague virus was studied. The tissue destruction and cellular response to RD virus were meagre. Heterophilic and monocytoid cell reaction was still the initial response. In duck plague infection there was progressive necrosis and this was associated with pronounced lymphoid reaction indicative of an immunologic reaction. In Ranikhet disease infection the lymphoid reaction was not as pronounced as in duck plague virus infection.